Sex Differences in the Regulation of Offensive Aggression and Dominance by Arginine-Vasopressin - Terranova, Joseph I.; Ferris, Craig F.; Albers, H. Elliott (Frontiers in Endocrinology, 2017)
Arginine-vasopressin (AVP) plays a critical role in the regulation of offensive aggression and social status in mammals. AVP is found in an extensive neural network in the brain. Here we discuss the role of AVP in the regulation of aggression in the limbic system with an emphasis on the critical role of hypothalamic AVP in the control of aggression. In males, activation of AVP V1a receptors (V1aRs) in the hypothalamus stimulates offensive aggression, while in females activation of V1aRs inhibits aggression. Serotonin (5-HT) also acts within the hypothalamus to modulate the effects of AVP on aggression in a sex-dependent manner. Activation of 5-HT1a receptors (5-HT1aRs) inhibits aggression in males and stimulates aggression in females. There are also striking sex differences in the mechanisms underlying the acquisition of dominance. In males, the acquisition of dominance is associated with the activation of AVP-containing neurons in the hypothalamus. In contrast, in females the acquisition of dominance is associated with the activation of 5-HT-containing neurons in the dorsal raphe. AVP and 5-HT also play critical roles in the regulation of a form of social communication that is important for the maintenance of dominance relationships. In both male and female hamsters AVP acts via V1aRs in the hypothalamus, as well as in other limbic structures, to communicate social status through the stimulation of a form of scent marking called flank marking. 5-HT acts on 5-HT1aRs as well as other 5-HT receptors within the hypothalamus to inhibit flank marking induced by AVP in both males and females. Interestingly, while AVP and 5-HT influence the expression of aggression in opposite ways in males and females, there are no sex differences in the effects of AVP and 5-HT on the expression of social communication. Given the profound sex differences in the incidence of many psychiatric disorders and the increasing evidence for a relationship between aggressiveness/dominance and the susceptibility to these disorders, understanding the neural regulation of aggression and social status will have significant import for translational studies.